2022
DOI: 10.1111/fwb.13906
|View full text |Cite
|
Sign up to set email alerts
|

The effect of trait‐based diversity on productivity results mainly from intraspecific trait variability in the macrophyte community

Abstract: Trait‐based methods are key to understanding the biodiversity–productivity relationship (BPR) of macrophyte communities. Community‐weighted mean traits (i.e., community trait structure) have been proven to have more influence on macrophyte community productivity than species richness. However, the underlying mechanism by which community trait structure variation affects macrophyte community productivity along an environmental gradient is still not well understood. A mesocosm experiment was used to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…The SEM approach allowed us to demonstrate that all traits considered except the LDMC had direct or indirect effects on individual performance. This observation is especially important, as the relationships between traits can influence individual performance (Pywell et al., 2003; Engbersen et al., 2022), in particular in macrophyte species (Fu et al., 2014; Ma et al., 2022b). Our findings support the current view in functional ecology of the relevance of multitrait approaches in which trait relationships are taken into account (Albert et al., 2010a; Blonder et al., 2014; Bittebiere et al., 2019; Gustafsson & Norkko, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEM approach allowed us to demonstrate that all traits considered except the LDMC had direct or indirect effects on individual performance. This observation is especially important, as the relationships between traits can influence individual performance (Pywell et al., 2003; Engbersen et al., 2022), in particular in macrophyte species (Fu et al., 2014; Ma et al., 2022b). Our findings support the current view in functional ecology of the relevance of multitrait approaches in which trait relationships are taken into account (Albert et al., 2010a; Blonder et al., 2014; Bittebiere et al., 2019; Gustafsson & Norkko, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Two decades ago, functional approaches emerged that allowed us to rebuild community ecology and establish general principles regarding assembly mechanisms (Calow, 1987; McGill et al., 2006). Since then, studies based on functional traits (morphological, physiological, and phenological characteristics that directly or indirectly impact individual performance through growth, reproduction, or survival) have been conducted in terrestrial (e.g., Garnier et al., 2001; Violle et al., 2007; Albert et al., 2010a), and aquatic plant communities (Yang et al., 2004; Fu et al., 2013, 2014; Luo et al., 2016; Su et al., 2019; Zhang et al., 2019; Chmara et al., 2021; Ma et al., 2022a, 2022b). Functional approaches have revealed that marked trait variation occurs in the field at inter‐ and intraspecific levels in response to a range of biological processes operating at different spatial and temporal scales, ultimately leading to species coexistence (Messier et al., 2010; Albert et al., 2010a; Taudiere & Violle, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous empirical studies have elucidated the nature of trait variation and have shown systematic relationships between traits and climatic and/or soil properties (Wright et al, 2005;Cornwell and Ackerly, 2009;Simpson et al, 2016). However, the dominant theories and methods of trait-based community ecology mainly focus on the differences in functional traits between species (Roscher et al, 2018), whereas the important role of intraspecific trait variation has been neglected (Siefert et al, 2015;Ma et al, 2022). Species with a widespread distribution tend to have greater trait variability and high intraspecific variation; moreover, they show a continuous geographic gradient, especially across different latitudes, as a consequence of acclimation to a broad range of environmental conditions (Siefert et al, 2015;Ren et al, 2020).…”
Section: Introductionmentioning
confidence: 99%